Perforated Gastric Ulcer Masquerading as Anterior Abdominal Wall Necrotizing Fasciitis - Firdaus Hayati; Nornazirah Azizan; Nik Amin Sahid; Hilal Zahabi Abdul Fattah; Rohamini Sibin; Andee Dzulkarnaen Zakaria (2020)
Necrotizing fasciitis (NF) is a deadly soft tissue infection causing a significant morbidity and mortality. Abdominal and chest wall NF are unusual. We describe a 49-year-old male with anterior abdominal wall NF secondary to perforated gastric ulcer (PGU). He was admitted in septic shock presenting an abdominal wall NF with severe metabolic acidosis requiring dialysis and admission to the intensive care unit. There was a patch of gangrene with surrounding skin discoloration at lower quadrant of the abdominal wall. Local debridement was done without a preoperative computed tomography that was performed after surgery. Adequate source control was not achieved after the second surgery and the patient had worsened resulting to death. We describe this rare presentation of NF and discuss the issues learnt from this unfortunate event.